Formulation And Characterization of Solid Soap Made from Seaweed (Padina minor) As an Antibacterial Agent - Abaidata, Riski; Naiu, Asri Silvana; Manteu, Shindy Hamidah (Jurnal Ilmiah PLATAX, 2025)
Padina minor is a type of brown algae from the Dictyotaceae family, which is a multicellular plant that lives in water. This study aims to formulate and characterize solid soap made from Padina minor seaweed as an antibacterial agent. The methods used include the extraction of bioactive compounds from Padina minor, making solid soap with different extract concentrations, as well as phytochemical testing, pH, foam stability, antibacterial activity against Staphylococcus aureus, and organoleptic testing of the resulting soap products. The results of the phytochemical analysis showed the presence of active compounds such as flavonoids, phenols, and saponins in the Padina minor extract. This study used a completely randomized design (CRD). This study consisted of three treatments with three replications of 10 mL, 15 mL, and 20 mL each. The results of the inhibition zone test showed that all solid soap formulations were able to inhibit the growth of Staphylococcus aureus with an average inhibition zone of 25.8 mm - 29.3 mm. The pH value of the solid soap was within the range of 9.7–9.8, meeting the pH standards for bath soap and demonstrating safe alkaline properties. Foam stability and organoleptic tests also showed good results and were accepted by the panelists. Based on the research results, solid soap made from Padina minor seaweed extract has the potential to be a safe and environmentally friendly natural antibacterial product. Keyword: Padina minor, solid soap, antibacterial, phytochemical, Staphylococcus aureus Abstrak Padina minor adalah salah satu jenis alga cokelat dari family Dictyotaceae, yang merupakan tumbuhan multiseluler yang hidup diperaian. Penelitian ini bertujuan untuk memformulasi dan mengkarakterisasi sabun padat berbahan dasar rumput laut Padina minor sebagai agen antibakteri. Metode yang digunakan meliputi ekstraksi senyawa bioaktif dari Padina minor, pembuatan sabun padat dengan konsentrasi ekstrak berbeda, serta pengujian fitokimia, pH, stabilitas busa, aktivitas antibakteri terhadap Staphylococcus aureus, dan uji organoleptik terhadap produk sabun yang dihasilkan. Hasil analisis fitokimia menunjukkan adanya senyawa aktif seperti flavonoid, fenol, dan saponin pada ekstrak Padina minor. Penelitian ini menggunakan rancagan acak lengkap (RAL). Penelitian ini terdiri atas tiga perlakuan dengan tiga ulangan masing-masing 10 mL, 15 mL, dan 20 mL. Hasil penelitian Uji zona hambat menunjukkan bahwa seluruh formulasi sabun padat mampu menghambat pertumbuhan Staphylococcus aureus dengan rata-rata zona hambat yaitu 25,8 mm – 29,3 mm . Nilai pH sabun padat berada dalam rentang 9,7–9,8, memenuhi standar pH sabun mandi dan menunjukkan sifat basa yang aman. Stabilitas busa dan uji organoleptik juga menunjukkan hasil yang baik dan diterima oleh panelis. Berdasarkan hasil penelitian, sabun padat berbahan dasar ekstrak rumput laut Padina minor berpotensi sebagai produk antibakteri alami yang aman digunakan serta ramah lingkungan. Kata Kunci: Padina minor, sabun padat, antibakteri, fitokimia, Staphylococcus aureus